Ovarian tissue autotransplantation improves longevity in mice - Ruhliada, Nikolai N. (Frontiers in Physiology, 2024)
In this study, we show the improvement in life longevity in an experimental mouse model after step-by-step autologous ovarian transplantation and compare its effects with exogenic transdermal estradiol usage. This has proven to be more efficient than “traditional” hormonal replacement therapy. Despite the high speed and effectiveness of estradiol replacement deficiency in blood by its oral or transdermal use, no significant increase in the life longevity of animals and possibly in women was noted. The function of the transplanted fragment is usually limited to 6–12 months. This is enough for oncofertility purposes, sometimes, but not for longevity improvement. We performed periodical tissue return (autologous transplantation), containing both the cortex and medulla in the experimental mouse model, which resulted in a statistically reliable improvement in longevity. Our experience indicates the important role of medullary ovarian factors in slowing the aging process in the body and increasing the life expectancy in the experiment. As shown, the transdermal estrogen supportive therapy for ovarian deficiency improves estrogen levels but causes much slower decreases in the follicle stimulating hormone (FSH) and luteinizing hormone (LH). Moreover, we attained the best longevity with step-by-step periodic ovarian autotransplantation, thus making “prosthetics” of ovarian function longer than it is preplanned physiologically [direct correlation between the levels of FSH and lifespan (r = 0.98)]. The experimental model we suggested could be projected to other mammals or humans as cortical transplantation provides the same results for reproduction restoration in mice and humans and even for hormone level normalization, but there is still a lack of information about anti-aging factors in the ovarian medulla and cortex. Hence, we consider that the most important factor for the anti-aging ovarian transplantation technology is to preserve and transfer both the medulla and cortex as parts of the whole ovary.